Edible Bird's Nest, a remarkable salivary product / Dr. Eddie Tan Ti Tjih and T. H. Siew - Tan Ti Tjih, Eddie; T. H., Siew (2021)
Edible Bird's Nest (EBN) is a salivary product, and it can only be produced by certain species of swiftlets in the Southeast Asia region. Even though the saliva product is not a popular delicacy among the non-Chinese community, its recent scientific nutraceutical discoveries have attracted much interest. There are many new findings reported on EBN in the recent ten (10) years; therefore, this discourse aims to address the latest peer-reviewed nutraceutical reports on the EBN. First, an advanced search in the Web of Science Core Collection with field tag keywords "Edible bird's nest" was performed. The search resulted in 129 articles for the year 2010 to 2020. Thus, the total number of yearly publications increased drastically from 1 article in the year-2010 to 23 articles in the year-2020. This indicates increasing interest in the research for EBN. Subsequently, the articles that met the EBN nutraceutical investigations criteria were reviewed.